2018
DOI: 10.1186/s12876-018-0750-x
|View full text |Cite
|
Sign up to set email alerts
|

Is perceived intolerance to milk and wheat associated with the corresponding IgG and IgA food antibodies? A cross sectional study in subjects with morbid obesity and gastrointestinal symptoms

Abstract: BackgroundSerum IgG and IgA food antibodies have been used for dietary advice to subjects with gastrointestinal symptoms and perceived food intolerance, but the role of these antibodies in mediating intolerance is controversial. The present study investigated associations between perceived gastrointestinal intolerance to milk-or wheat and the corresponding s-IgG and s-IgA food antibodies in subjects with morbid obesity.MethodsSubjects with morbid obesity (BMI ≥ 40 kg/m2 or ≥35 kg/m2 with obesity-related compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Gluten and IgG reactions might be associated with systemic inflammation [34] and contribute to the pathophysiology of IBS [38]. Furthermore, the literature suggests that overweight and obese subjects tend to have a higher frequency of GI comorbidity [39]. Barley, and its components, also appear to play an important role in obesity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Gluten and IgG reactions might be associated with systemic inflammation [34] and contribute to the pathophysiology of IBS [38]. Furthermore, the literature suggests that overweight and obese subjects tend to have a higher frequency of GI comorbidity [39]. Barley, and its components, also appear to play an important role in obesity [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological and uncontrolled studies have confirmed IgG hyperresponsiveness to dietary antigens in patients with IBS [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In addition, the role of specific IgG4 subclasses in food antigens was confirmed in childhood [ 27 ], adults with IBS [ 28 , 30 , 31 ] and those with migraine combined with IBS [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies even found an association between food hypersensitivity and inflammation in the gut, obesity or functional disorders [ 33 ]. However, most studies demonstrated controversial and unconvincing results regarding eliminating diets in IBS and other conditions [ 29 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It's difficult to say the serum specific IgG antibodies are the cause or results of GI symptoms. On the one hand, increased gut permeability could potentially result in elevated levels of the food antibodies, while there was an inverse association between tight-junctional gut permeability and perceived food intolerance ( 37 ), suggesting other underlying mechanism for the concentrations of antibodies. On the other hand, GI symptoms are only a clinical manifestation, which could be caused by digestive disease, intestinal flora disturbance, or even organic disease.…”
Section: Discussionmentioning
confidence: 99%